2021
DOI: 10.7774/cevr.2021.10.3.298
|View full text |Cite
|
Sign up to set email alerts
|

Acute urticarial rash after COVID-19 vaccination containing Polysorbate 80

Abstract: We present the case of a 48-year-old Caucasian woman, who developed an acute urticarial rash after the second dose of coronavirus disease 2019 (COVID-19) vaccination with Oxford-AstraZeneca. Though the most common cutaneous adverse reactions to vaccines are non-allergic, we believe the rash may represent an immediate hypersensitivity type I reaction against the vaccine excipient Polysorbate 80 (Pol80), configuring an acute allergic urticaria. Skin prick test with Pol80, were performed and resulted positive, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Nonetheless, dermatologists should be aware of this and all other possible cutaneous reactions associated with the COVID-19 vaccine, to promptly recognize and, if needed, treat them, minimizing the discomfort of the patients and thereby encouraging the population to undergo vaccination. 11,12 Lastly, we highlight the importance of reporting adverse reactions,…”
Section: Discussionmentioning
confidence: 94%
“…Nonetheless, dermatologists should be aware of this and all other possible cutaneous reactions associated with the COVID-19 vaccine, to promptly recognize and, if needed, treat them, minimizing the discomfort of the patients and thereby encouraging the population to undergo vaccination. 11,12 Lastly, we highlight the importance of reporting adverse reactions,…”
Section: Discussionmentioning
confidence: 94%
“…Ten out of 21 developed macular or urticarial rashes, which resolved with antihistamine or spontaneously, similarly to cases reported in the literature. 2 , 3 , 4 , 5 , 6 Two patients presented generalized pruritic rash shortly after vaccination (≤4 h), possibly representing immediate hypersentivity type I reactions against vaccine excipients. 2 , 3 , 4 , 5 , 6 …”
Section: Discussionmentioning
confidence: 99%
“… 2 , 3 , 4 , 5 , 6 Two patients presented generalized pruritic rash shortly after vaccination (≤4 h), possibly representing immediate hypersentivity type I reactions against vaccine excipients. 2 , 3 , 4 , 5 , 6 …”
Section: Discussionmentioning
confidence: 99%
“…In cases where the same sample was used for more than one study, all studies were reviewed to determine the extent to which there may be duplication in the reported outcomes between studies. The full text of selected studies was reviewed, and data on demographics, article type, number of reported cases with cutaneous involvement, vaccine, and rash type (morphology) were extracted from articles texts, tables, figures, and summarized through a descriptive table (Table 1)…”
Section: Methodsmentioning
confidence: 99%